Enjeux futurs pour le français et le francoprovençal dans la Suisse plurilingue à la lumière des données de la dernière Enquête sur la langue - Spagna, Maria Immacolata (Ponti/Ponts, 2024)
Unlike other States, which are officially monolingual, Switzerland is distinguished by its constitutional quadrilingualism. In this multilingual society, the preservation of linguistic diversity and mutual intelligibility between the communities of the different linguistic regions are among the main objectives of the federal State. With the aim of monitoring the complex linguistic situation, the languages spoken by the population have been reviewed for some time in Switzerland. After the reform of 2010, every five years since 2014, the data collected in the Enquête sur la langue, la religion et la culture make it possible to learn about linguistic practices and habits as well as the views of the Swiss regarding languages. Furthermore, the latest Enquête (2021), on which this contribution will be based, allows one to compare the data collected in 2019 with the results of 2014, thus providing the possibility of following the linguistic evolution of recent years, determinated above all by the Maria Immacolata Spagna 216 increase of non-native languages and even more by the unstoppable ascension of English. After a quick look at the past, when for centuries in French-speaking Switzerland Francoprovençal was the vehicle of communication and French the written language, we will trace the current status of these languages to see what future challenges language policy must face to support them. By respecting the fundamental principles of the Constitution, the teaching of plurilinguism could act effectively for the preservation and promotion of traditional languages such as Francoprovençal and French but also for those of the entire linguistic heritage of Switzerland.